Praktik Jasa Convert Pulsa Jadi Uang Pandangan Hukum Islam (Study di Instagram Master Voucher) - Andriansyah, Muhammad; Winarsih, Tri; Fikri, Arif (ASAS, 2022)
Convert which has the meaning of "to change" means to completely change the pulse. This form of credit change is found in the results of converting pulses that can be used as other means of payment, either in cash or digitally. The objectives to be achieved in this study are to find out the practice of using the service of converting pulses into money on master.voucher and to find out the views of Islamic law on the practice of converting credit into money. This type of research uses field research (Field Research). Data collection techniques by observation, interviews, and documentation. Data processing method with editing, organizing, and analizing. Based on the results of research on the use of credit-to-money converting services in Instagram Master. Voucher Social Media, the author can draw the following conclusions: The use of credit-to-money exchange services is a sought-after solution, especially for those who have excess credit. Credit is the main requirement for mobile phones to be used as a liaison medium so that they can communicate at near and far distances. In addition to communicating, pulses can also be used to carry out various transactions; According to Islamic law, the use of credit-to-money converting services has been carried out in accordance with the provisions of Islamic law. Because the use of this credit converting service has fulfilled the basic laws and pillars of the contract in Islam.Keyword: Islamic Law, Convert Pulsa, Convert Credit